VD_FINDINFO ML / 2018 / 169 vom 11. Oktober 2018 - VD Tribunal cantonal (2018)
MAINLEVÉE DÉFINITIVE, DÉCISION EXÉCUTOIRE, CHOSE JUGÉE | 80 al. 1 LP, 336 al. 1 let. a CPC (CH), 336 al. 1 let. b CPC, 336 al. 2 CPC (CH)